Immune Modulation to Enhance Bone Healing—A New Concept to Induce Bone Using Prostacyclin to Locally Modulate Immunity - Wendler, Sebastian; Schlundt, Claudia; Bucher, Christian H.; Birkigt, Jan; Schipp, Christian J.; Volk, Hans-Dieter; Duda, Georg N.; Schmidt-Bleek, Katharina (Frontiers in Immunology, 2019)
Within an aging population, fracture incidences will rise and with the augmented risks of impaired healing the overall risk of delayed bone regeneration will substantially increase in elderly patients. Thus, new strategies to rescue fracture healing in the elderly are highly warranted. Modulating the initial inflammatory phase toward a reduced pro-inflammation launches new treatment options for delayed or impaired healing specifically in the elderly. Here, we evaluated the capacity of the prostacyclin analog Iloprost to modulate the inflammatory phase toward a pro-regenerative milieu using in vitro as well as in vivo model systems. In vitro, Iloprost administration led to a downregulation of potential unfavorable CD8+ cytotoxic T cells as well as their pro-inflammatory cytokine secretion profile. Furthermore, Iloprost increased the mineralization capacity of osteogenic induced mesenchymal stromal cells through both direct as well as indirect cues. In an in vivo approach, Iloprost, embedded in a biphasic fibrin scaffold, decreased the pro-inflammatory and simultaneously enhanced the anti-inflammatory phase thereby improving bone healing outcome. Overall, our presented data confirms a possible strategy to modulate the early inflammatory phase in aged individuals toward a physiological healing by a downregulation of an excessive pro-inflammation that otherwise would impair healing. Further confirmation in phase I/II trials, however, is needed to validate the concept in a broader clinical evaluation.